PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN GENERASI Z PADA PT CIPTA NINDITA NUSAPALA JAKARTA TIMUR - Fatmi Dian Rahayu; Shella Puspita Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of transformational leadership and job training on the performance of Generation Z employees at PT Cipta Nindita Nusapala, East Jakarta. This research uses a quantitative approach with multiple linear regression analysis methods. The research data were obtained through questionnaires distributed to Generation Z employees working in the company. The independent variables in this study are transformational leadership and job training, while the dependent variable is employee performance. The regression analysis results indicate that transformational leadership and job training have a positive influence on employee performance. The regression coefficient of transformational leadership is 0.339, indicating that improvements in transformational leadership can enhance employee performance. Meanwhile, the regression coefficient of job training is 0.389, showing that job training has a greater effect in improving employee performance. The results of this study indicate that the implementation of effective transformational leadership and appropriate job training programs for Generation Z employees can significantly improve employee performance. Therefore, companies are expected to enhance leadership quality and provide continuous training programs to improve employee performance and productivity.